Analisis Prediksi Kebangkrutan Perusahaan Asuransi di Bursa Efek Indonesia Menggunakan Model Altman Z-Score - Sansivani Suvanissa; Fithri Sri Mulyani; Ahmad Fitri (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
With the increasing economic uncertainty and claims risk that can affect the solvency level of companies, evaluating the financial condition of insurance companies becomes important. Management and regulators need to use analyzes that can identify bankruptcy risks early to make decisions.This study aims to analyze the financial condition of insurance companies listed on the Indonesia Stock Exchange for the 2021–2025 period using two main indicators, namely Risk Based Capital (RBC) and Altman Z-Score. The research method used is quantitative with a descriptive approach based on secondary data from annual financial reports. The results of the study show that most insurance companies have RBC above the minimum requirement of the Financial Services Authority (OJK) of 120%, with VINS and ABDA recording the highest RBC of 1,685.96% and 744.06% in 2025. Based on the modified Altman Z-Score, of the eight insurance companies studied, four companies are in the safe category, namely PT.AMAG, PT.ABDA, PT.VINS and PT.AHAP. And the other four are in the gray zone category, namely PT.YOII, PT.ASBI, PT.MREI and PT.ASDM. The conclusion of this study is that the majority of insurance companies have healthy financial conditions during the 2021–2025 period, with liquidity management, profitability, and capital structure being key factors in reducing bankruptcy risk.